Financial Literacy and Financial Outcome of Microenterprises in the Province of Bulacan - Corpuz, Jr, Gerardo A (ASEAN Multidisciplinary Research Journal, 2022)
Financial literacy enables owners of microenterprises to understand and assess their financial outcome and make reasonable financial decisions. The paper explores the financial literacy of owners of microenterprises in the Province of Bulacan and how literacy influences the financial outcome of their businesses. The study apopulation were owners of registered micro business in Bulacan from the Department of Trade and Industry, out of which a sample of 296 was selected through the simple random sampling technique. The data was analyzed using percentage and frequency, weighted mean and Pearson-R. The results showed a positive relationship between financial literacy and the financial outcome of micro-enterprises (r= .730, p< .001). The paper recommends that policy makers should specifically design a program and platform targeted at further improving the financial literacy level of micro business owners to help increase the financial performance of their enterprises.